Effectiveness of a sexual and reproductive health and HIV prevention program for Thai early adolescents: Youth empowerment and participation - Warunee Fongkaew (2018)
Young people are at the center of the HIV/AIDS epidemic globally. Thailand is similar to many other countries in this regard as experiencing a high prevalence of sexually-transmitted diseases among Thai adolescents. Innovative and effective strategies are needed to prevent risk-taking behavior at the earliest period of adolescence before unhealthy patterns are established. The aim of this study was to empower youth leaders in developing and implementing activities for sexual and reproductive health education and HIV prevention among Thai early adolescents, using the youth and adult partnership with schools (YAPS) approach. Twelve schools from three different educational areas in Chiang Mai participated in this participatory action research. Qualitative and quantitative data were collected, using various methods. Results showed that this peer education program was effective in empowering junior youth leaders to conduct peer-led activities with early adolescents in grades 5 to 7. Junior youth leaders developed participatory learning activities and created innovative media materials including cartoon books, websites, radio broadcasting, VCDs and an educational computer game. The scores of HIV/AIDS knowledge and attitudes towards sexual behaviors among target peers significantly increased after implementing peer-led activities in 12 schools (p=.05). The use of partnerships and the participatory process mobilized parents, teachers and school administrators to play a proactive role in sexual education and HIV prevention for early adolescents in schools, resulting in the integration of the program into the school system, thereby assuring its sustainability.